STUDY ON HAEMATO-BIOCHEMICAL AND OXIDATIVE STRESS IN EXPERIMENTALLY INDUCED KETOPROFEN TOXICITY IN WISTAR RATS - fefar, DT; Khanpara, YJ; Joshi, DV; Patel, BJ; Modi, SK (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
The present research work was conducted to study the haemato-biochemical and oxidative stress effect of subacute intramuscular administration of ketoprofen for 14 days on 24 female Wistar rats. The animals were equally divided into 4 different groups A, B, C, D during randomization and dosed with vehicle control, 4 mg/kg as low dose, 8 mg/kg as mid dose and 12 mg/kg as high dose of ketoprofen, respectively. The drug was administered by intramuscular route every day for 14 days. At the end of 14 days treatment, all the animals from group A to D were subjected to blood collection and haemato-biochemical and oxidative stress investigation. The haematological study revealed dose dependent decrease in Hb, PCV,TEC, lymphocyte per cent and MCHC in Group C and Group D rats, while increase in MCV and neutrophil per cent in Group C and Group D rats.Administration of ketoprofen caused reduction in serum total protein (Group C and Group D), albumin (Group C and Group D) and globulin (Group D) in different groups. The result suggested that long term administration of ketoprofen at dose rate of 8 mg/kg and 12 mg/kg leads to macrocytic hypochromic anaemia possibly because of gastrointestinal bleeding or micro-bleeding and it is also evident that ketoprofen at the dose rate of 8 mg/kg b.wt. and 12 mg/kg b.wt. results into oxidative stress.